Exploring, What is a "Nursing Expert" - Hibbard, Danielle (My University, 2015)
The goal of this project was a review of the nursing literature to determine if Fehring's (1994) criteria remains relevant in defining nurse expert for the purposes of nursing diagnosis validation.
Color poster with text, images, and graphs.
Keywords: Nursing literature; Nursing leadership; Nursing expertise; Posters